The Impact of Inflation, Poverty Rates and Unemployment on Indonesia’s Economic Growth, with the Human Development Index as an Intervening Variable - winda sari siregar; Rukiah; Budi Gautama Siregar (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2026)
Indonesia's economic growth conditions according to data presented by BPS in the 2018-2024 period, namely the period before and after the Covid-19 event tended to stagnate at around 5 percent per year. There are several macroeconomic problems that cause low Indonesian economic growth, including inflation, poverty rates, and unemployment, as well as the Human Development Index (HDI). This type of research is a quantitative causality approach with time series data. The research period is 2028-2024 in Indonesia. The population in this study is Indonesian economic growth data reflected in GDP, inflation, poverty rates, unemployment, and HDI from 2018-2024 in the form of monthly data. So the population in this study is 84. The sampling technique used is saturated sampling, namely all 84 populations are used as samples. Data analysis techniques used are normality tests, multicollinearity, heteroscedasticity, autocorrelation, coefficient of determination tests, partial tests, simultaneous tests, and Sobel tests. The findings in this study are that inflation and unemployment do not affect the HDI, poverty affects the HDI, there is an influence of the HDI, inflation, and poverty on economic growth, and the HDI cannot mediate the relationship between inflation, unemployment and economic growth, and there is an influence of poverty on economic growth mediated by the HDI